HPV infecton and lesion prevention using HPV vaccine - Giraldo, Paulo C.; Silva, Maria José P.M.A.; Fedrizzi, Edison N.; Gonçalves, Ana Katherine S.; Amaral, Rose Luce G.; Eleutério Junior, José; Figueiredo, Iaponira V. (Brazilian Journal of Sexually Transmitted Diseases, 2008)
The discovery of a vaccine capable of altering the natural course of cervical and other cancers resulting from HPV infection, not only has great perspectives in the medical community but also among the different segments of the population. Due to this, is now participates in the immunization schedules of various countries. The aim of this paper is to review the fact that the prophylactic vaccine against HPV, which although alone is not able to completely eliminate cervical cancer, can, in fact bring an important contribution to public health, when associated to screening programs for cervical cancer. Even knowing the high efficacy of prophylactic vaccines against specific types of HPV, further studies, to assess the results in the long term, will be required, since the longest term studies up to press have only reached an 9.5 year follow up period. So far, the results suggest no need for a vaccine booster, however a greater than ten year follow up period will be necessary to evaluate efficacy, safety time lapse and time of validity of the prophylactic vaccine against HPV.